Farming systems research at the International Agricultural Research Centres and other international groups - Anderson, F.M.; Dillon, John L. (Australian Centre for International Agricultural Research, 1985)
Presents Simmond's recent classifiation of Farming Systems Research followed by overviews of the FSR in progress at several International Agriculural Research Centres. Summarises the activities of 10 centres involved in Farming Systems Research in eastern and southern Africa. Discusses the issues in adoption of FSR by the National Agricultural Research Systems Research.